2019
DOI: 10.1021/acs.jpcc.9b05237
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Reaction of Nitric Oxide on the Rh5V+ Cluster: A Density Functional Theory Mechanistic Study

Abstract: Recent experiments on the reaction of metal-doped Rh clusters with NO indicate that V-doping is the most effective for the NO decomposition. The reaction mechanism of NO molecules on Rh 5 V + cations was studied using density functional theory calculations in the present work. The first NO molecule adsorbs on the Rh 5 V + cluster and decomposes into O and N atoms to form the V−O bond, with a low barrier of 19.76 kcal/mol. The V−O affinity strongly promotes NO dissociation. There are two alternative reaction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…From the point of view of general chemistry, the fundamentals of adsorption, dissociation, reduction, oxidation, and disproportionation of small gas molecules on transition metal surfaces and clusters have been extensively studied in previously published studies. For example, Mafuné et al tested the reactions of Rh n + clusters with NO under thermal equilibrium conditions and found the generation of a series of molecular and dissociative NO-adsorption products as well as N 2 -release products at high temperatures. Kondow et al and Mackenzie et al , observed the loss of Co atoms or CoN 2 moieties along with the N 2 release for small Co n + clusters in FT-ICR experiments, whereas they found that the larger Co n + clusters showed NO adsorption without fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of general chemistry, the fundamentals of adsorption, dissociation, reduction, oxidation, and disproportionation of small gas molecules on transition metal surfaces and clusters have been extensively studied in previously published studies. For example, Mafuné et al tested the reactions of Rh n + clusters with NO under thermal equilibrium conditions and found the generation of a series of molecular and dissociative NO-adsorption products as well as N 2 -release products at high temperatures. Kondow et al and Mackenzie et al , observed the loss of Co atoms or CoN 2 moieties along with the N 2 release for small Co n + clusters in FT-ICR experiments, whereas they found that the larger Co n + clusters showed NO adsorption without fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have been motivated by the use of rhodium in automotive three-way catalytic converters 9 and the reactions of N 2 O, [10][11][12] NO, [13][14][15][16][17][18][19][20][21][22] CO 23,24 and CO 2 25 have been extensively investigated on both pure and doped [26][27][28] rhodium clusters. Given that spectroscopic methods such as infrared multiple photon dissociation spectroscopy (IRMPD) 29 use mass spectroscopy to identify the species of interest, they generally provide information only about the products of reactions and reactivity studies therefore often include computational investigation, 30,31 typically using density functional theory (DFT), but sometimes including higher level methods such as CCSD(T).…”
Section: Introductionmentioning
confidence: 99%
“…The study of transition metal cluster superatoms is of great significance because of their unique reaction inertia and structural stability, including open‐shell superatom Cu 18 − [12], double magic cluster Ag 17 − [13], tetrahedral Pt 10 − [14] and neutral vanadium cluster V 10 [15]. Transition‐metal nanoclusters have demonstrated good catalytic activity in the removal of NO [16–21]. For example, Begum et al [16] studied the adsorption of nitric oxide (NO) molecule on neutral, cationic, and anionic Pd n ( n = 1–5) clusters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Begum et al [16] studied the adsorption of nitric oxide (NO) molecule on neutral, cationic, and anionic Pd n ( n = 1–5) clusters. Zhao et al [17] successfully dissociated NO into N 2 and O 2 using Rh‐doped V clusters. Arab et al [18] explored the adsorption and dissociation of NO on Rh x Cu 4− x ( x = 0–4) nanoclusters and found that the nitrogen end of NO has a stronger affinity to adsorb on the Rh atom(s) of the clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation